Performance and selectivity of lower-rim substituted calix[4]arene as a stationary phase for capillary gas chromatography. Issue 37 (8th July 2019) - Sun, Tao; Li, Bin; Shuai, Xiaomin; Chen, Yujie; Li, WeiWei; Cai, Zhiqiang; Qiao, Xiaoguang; Hu, Shaoqiang; Ma, Lufang
Abstract : This work presents the investigation of p-tert -butyl(tetradecyloxy)calix[4]arene (C4A-C10) as stationary phase for capillary gas chromatographic (GC) separations. Abstract : This work presents the investigation of p-tert -butyl(tetradecyloxy)calix[4]arene (C4A-C10) as stationary phase for capillary gas chromatographic (GC) separations. The statically-coated C4A-C10 capillary column showed weak polarity and column efficiency of 2566 plates per m determined by n -dodecane at 120 °C. Impressively, the C4A-C10 column exhibited extremely high resolving capability for a wide range of analytes from nonpolar to polar, including n -alkanes, esters, ketones, aldehydes, alcohols and bromoalkanes. Most importantly, the C4A-C10 column exhibited an excellent separation performance for positional, structural and cis -/ trans -isomers. Among them, the column displayed advantageous resolving capability over the commercial polysiloxane stationary phase for aromatic amine isomers. Moreover, the C4A-C10 column showed good column repeatability with RSD values below 0.06% for run-to-run, 0.12–0.27% for day-to-day and 2.8–5.3% for column-to-column.